KOMBINASI CAMPURAN PELEPAH KELAPA SAWIT DAN KULIT KACANG TANAH SEBAGAI BAHAN BAKU PEMBUATAN BIOBRIKET - Darni Paranita (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2020)
This study used oil palm fronds and peanut shells with a carbonization temperature of 300 0C for 15 minutes, and the adhesive used in this study was tapioca flour with a content of 15% by weight of the briquette. The aim of this research is to make charcoal briquettes which are useful as an alternative fuel replacement. The charcoal formed is crushed and sieved to make the similar size (60 mesh) then the charcoal is weighed with a combination of a mixture of palm frond charcoal and peanut shell charcoal, 80%: 20%, 50%: 50%, 40%; 60% and 20%: 80%. Quality testing includes water content, ash content and heating value. The optimal fuel value produced in a mixture combination of 80%: 20% is worth 5662.7 cal / gr